Pilot outdoor cultivation of a marine haptophyte Tisochrysis lutea using a novel floating photobioreactor driven by electric rotary motor - Fujii, Masashi; Takayama, Yoshiki; Tomatsu, Chiaki; Sano, Kashu; Kishinami, Hidemi; Hirahara, Minamo; Farahin, Abd Wahab; Harun, Razif; Yusoff, Fatimah Md; Syukri, Fadhil; Furuya, Ken; Toda, Tatsuki (Elsevier B.V., 2025)
Floating photobioreactors have recently attracted attention to utilize water surface areas such as estuaries, oceans, lakes, aquaculture ponds for microalgae biomass production. Outdoor cultivations of Tisochrysis lutea with a novel floating oscillation photobioreactor, named CRADLE, were conducted in triplicates under tropical climatic setting in Malaysia. The batch cultivations were performed in September 2022, November 2023, and March 2023. Biomass and fucoxanthin were analyzed using culture aliquot sampled every morning. The maximum dry weights of T. lutea were 0.99 ± 0.11–1.1 ± 0.0 g L−1under continuous mixing in November 2022 and March 2023. The dry weight and fucoxanthin yield under continuous mixing were significantly higher than that achieved under intermittent mixing (p < 0.05). Additionally, the November 2022 and March 2023 experiments showed higher maximum dry weight than that in September 2022 due to the supplementation of 0.01 M NaHCO3. Considering the energy cost of mixing, the CRADLE demonstrated a 65.9–71.1 % reduction in mixing energy compared with aerated cultivation with bubble column photobioreactor and obtained fucoxanthin productivity per unit of mixing energy within the range of 1.2 ± 0.08–3.6 ± 0.48 mg kWh−1under continuous oscillation mixing. Overall, these results contribute to the understanding of how oscillation mixing affects microalgae production and fucoxanthin accumulation. The CRADLE, which uses the electric rotary motor for culture mixing, reduced mixing cost and did not require temperature control, thereby demonstrating its potential for energy-saving microalgal cultivation.